Efficacy of antioxidant vitamins in Alzheimer’s and Parkinson’s disease, particularly in the period after the SARS-COV-2 pandemic - Bolesławska, Izabela A.; Werblińska, Alicja; Bolesławska-Król, Natasza; Żwirska, Jaśmina; Ostachowska-Gąsior, Agnieszka; Przysławski, Juliusz (Family Medicine & Primary Care Review, 2025)
The progressive changes in neuronal function and morphology, disruption of brain homeostasis and damage to signaling pathways in Alzheimer’s disease (AD) and Parkinson’s disease (PD) lead to deterioration of motor and psycho-behavioral performance, becoming a huge burden for patients and their families and posing new challenges to the healthcare system. The unprecedented healthcare landscape associated with the SARS-CoV-2 pandemic has increased the prevalence of neurodegenerative diseases and drawn attention to non-pharmacological methods of prevention and treatment. One candidate that may reduce the incidence and clinical manifestations of AD and PD patients, while alleviating the course of COVID-19, are vitamins. Some of them may also slow the progress of the patient’s disease by affecting neurogenesis, reducing inflammation, enhancing the immune system. The purpose of this research was to review current scientific literature to assess the efficacy of vitamins A, C, E, and D in preventing and supporting the treatment of Alzheimer’s disease and Parkinson’s disease. The review concluded that an insufficient dietary supply of vitamins A, C, D, and E may increase the risk of COVID-19 and the occurrence of AD and PD. However, results on the benefits of antioxidant vitamin supplements in AD and PD are inconclusive, with the exception of the effect of vitamin E in preventing PD-induced neurodegeneration and the beneficial effect of vitamin A in AD patients. There are no clinical recommendations for their use. A well-balanced diet with a high antioxidant profile becomes the best recommendation.